Decay in Relation to Management of Dry Coppice Teak Forests - Singh, Sujan; Puri, Y. N.; Bakshi, B. K. (Indian Forester, 1973)
In dry teak (Tectona grandis Linn. f.) forests in Gujarat state, the present system of coppicing flush with the grouad results in about 50 percent of trees becoming decayed at the end of the rotation. The decay is present in the lower part of the trees and may extend up tn 2-4m on the stem. Any, form of felling, including coppicing, results in injuries through which decay, establishes in the stools. Such decay migrates into callus shoots and high side shoots which constitute about 80 per cent of the present crop, because of the intimate heartwood conneciion established between the shoot and the stool. Low side shoots which constitute about 20 percent of the crop, however, remain free from decay as the heartwood connention with the stool is not established. Coppice teak forests sbould therefore be managed in a way that low side shoots are encouraged to develop and constitute the ultimate crop. Low copplcing results in cutting away of dormant buds which are present at the base of the tree and thus affect the sprouting at that level affecting frequency of low side shoots. In high coppicing, development of callus shoots is inhibited due to rapid drying and shrinkage of wood at the cut surface, causing separation from the bark. Also in high felling in a dry locality, even if the upper part dies the base of the stem remains alive to encourage development of side shoots. Based on the above premises, experiments were laid down in Godhra Forest Div., Gujarat State, where coppicing was done at different heights adjusting coppicing heights from ground leve1 to 25 cm at intervals of 5 cm. Copplcing at 10-15 cm was found ideal when low side soots were encouraged while callus and high side shoots discouraged to develop. Also, at these heights, adequate number of stools with low side shoots became available to select maximum number of low side shoots evenly distributed in the stand. Cleaning in the fifth year as is currently practised may continue as both callus aud side shoots may develop with equal vigour at all ages. It is, therefore, concluded that in dry teak forests, the stool heights may be adjusted at 10-15 cm from ground level and low side shoots selected for raising a healthy coppice crop free from decay.